Soda-lime glass via processing method, soda-lime glass via processing alkaline etching solution, and soda-lime glass having a via
Patent Information
- Application Number
- CN202611062485.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-16
AI Technical Summary
传统碱性刻蚀液刻蚀速率极慢,钠钙玻璃无法通过激光诱导后单次刻蚀实现直通,量产效率低下
[0007] This application embodiment utilizes an alkaline etching solution composed of a chelating agent (a polyamino-polyphosphonic acid chelating agent and/or its salt chelating agent containing at least two amino groups and at least two phosphonic acid groups) and an inorganic strong base, a wetting agent, and an alkanolamine-based agent. The process involves the interaction of multiple amino and phosphonic acid groups in the chelating agent molecule with the Ca released from the soda-lime glass. 2+ Mg 2+ It forms a stable, soluble, multidentate chelate, thus blocking the Ca2+ at its source. 2+ /Mg 2+ The pathway involves combining with silicate ions to form insoluble silicate precipitates. Meanwhile, alkanolamine additives have the functions of assisting chelation, wetting and penetration, and pH buffering. Together with wetting agents, they reduce the surface tension of the etching solution and improve the mass transfer uniformity in micropores with high aspect ratios. This enables through-hole formation of soda-lime glass with a thickness of 1.1 mm or less under alkaline conditions. That is, through-hole formation is achieved in a single etching based on the continuous laser modification route. The etching rate is effectively improved compared with traditional alkaline solutions. The roughness of the inner wall of the through-hole is low and there is no precipitation blockage, which significantly improves the efficiency and yield of TGV processing.
Smart Images

Figure CN122916446A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of glass substrate processing technology, and particularly relates to a method for processing through holes in soda-lime glass, an alkaline etching solution for processing through holes in soda-lime glass, and soda-lime glass with through holes. Background Technology
[0002] Through-glass via (TGV) technology is one of the core processes in fields such as 3D packaging, display substrates, and microfluidic devices. Soda-lime glass, due to its low cost and high adaptability, has broad application prospects in these fields. The current mainstream TGV process route combines laser modification with wet etching: first, a laser is used to create continuously modified microchannels inside the glass; then, the glass is immersed in an etching solution, and the difference in etching rates between the modified and unmodified areas is used to selectively dissolve the modified areas, ultimately forming the through-hole.
[0003] In existing technologies, alkaline etching solutions (mainly NaOH / KOH) or acidic etching solutions (hydrofluoric acid system) are commonly used to etch glass substrates. Traditional alkaline etching solutions have extremely slow etching rates, making it impossible to achieve through-cutting of soda-lime glass in a single laser-induced etching process, resulting in low mass production efficiency. Under alkaline etching conditions, the Ca released after the glass network dissolves... 2+ Mg 2+ With silicate ions (SiO3) 2- The combination of these substances produces insoluble calcium silicate (CaSiO3) and magnesium silicate (MgSiO3) precipitates. These precipitates deposit within the laser-modified micropores, causing pore shrinkage, blockage, and excessively large cone angles, and in severe cases, making it impossible to form through-holes. The hydrofluoric acid system has an extremely fast etching rate for conventional glass substrates (often exceeding 100µm / h), but it has the following defects when used for through-hole processing of soda-lime glass: (1) Soda-lime glass contains a high content of Ca 2+ Mg 2+ (Existing in the form of CaO and MgO), in the hydrofluoric acid system, the Ca in soda-lime glass... 2+ With F - The reaction generates a large amount of insoluble CaF2 precipitate, which rapidly blocks the micropores and severely damages the surface morphology.
[0004] To address the precipitation problem during etching, it has been reported to add complexing agents to the etching solution. For example, carboxylic acid complexing agents (such as sodium gluconate, sodium citrate, and sodium ethylenediaminetetraacetate) are added to alkaline etching solutions in an attempt to chelate Ca2+. 2+ Mg 2+ Inhibits silicate precipitation. However, these carboxylic acid complexing agents are easily decomposed and deactivated in alkaline environments at high temperatures (80~110℃), affecting the precipitation of Ca. 2+ / Mg 2+The chelating ability is limited and cannot effectively prevent the formation of silicate precipitation; at the same time, the increase in etching rate is minimal, and it still takes several hours or even longer to etch through thin glass. After etching, the roughness of the inner wall of the through hole is difficult to meet the subsequent metallization requirements (usually ≤100nm), and the through-hole effect of thick glass cannot be achieved. Summary of the Invention
[0005] In order to overcome the problems existing in the prior art, the main objective of this application is to provide a method for processing through holes in soda-lime glass, an alkaline etching solution for processing through holes in soda-lime glass, and soda-lime glass with through holes.
[0006] To achieve the above-mentioned objectives, the technical solution adopted in this application is as follows: In a first aspect, this application provides a method for processing through holes in soda-lime glass, comprising the following steps: Laser modification is performed on the target area of the soda-lime glass to form a modified area that penetrates the soda-lime glass; The modified area is etched using an alkaline etching solution to form a through hole; The raw materials of the alkaline etching solution include an inorganic strong base, a chelating agent, a wetting agent, an alkanolamine agent, and water; the chelating agent includes polyamino polyphosphonic acid chelating agents and / or their salts containing at least two amino groups and at least two phosphonic acid groups.
[0007] This application embodiment utilizes an alkaline etching solution composed of a chelating agent (a polyamino-polyphosphonic acid chelating agent and / or its salt chelating agent containing at least two amino groups and at least two phosphonic acid groups) and an inorganic strong base, a wetting agent, and an alkanolamine-based agent. The process involves the interaction of multiple amino and phosphonic acid groups in the chelating agent molecule with the Ca released from the soda-lime glass. 2+ Mg 2+ It forms a stable, soluble, multidentate chelate, thus blocking the Ca2+ at its source. 2+ / Mg 2+ The pathway involves combining with silicate ions to form insoluble silicate precipitates. Meanwhile, alkanolamine additives have the functions of assisting chelation, wetting and penetration, and pH buffering. Together with wetting agents, they reduce the surface tension of the etching solution and improve the mass transfer uniformity in micropores with high aspect ratios. This enables through-hole formation of soda-lime glass with a thickness of 1.1 mm or less under alkaline conditions. That is, through-hole formation is achieved in a single etching based on the continuous laser modification route. The etching rate is effectively improved compared with traditional alkaline solutions. The roughness of the inner wall of the through-hole is low and there is no precipitation blockage, which significantly improves the efficiency and yield of TGV processing.
[0008] Secondly, this application provides an alkaline etching solution for processing through-holes in soda-lime glass. The raw materials of the alkaline etching solution for processing through-holes in soda-lime glass include an inorganic strong alkali, a chelating agent, a wetting agent, an alkanolamine agent, and water. The chelating agent includes polyaminopolyphosphonic acid chelating agents and / or their salts.
[0009] The alkaline etching solution in this application uses an inorganic strong alkali as the main etching agent, providing a high concentration of OH... - The ions efficiently disrupt the Si-O-Si network framework of soda-lime glass. Simultaneously, the core functional components are polyamino-polyphosphonic acid chelating agents and / or their salts. The molecules contain at least two amino groups and at least two phosphonic acid groups, enabling them to interact with the Ca²⁺ released during the etching process of soda-lime glass through nitrogen atoms and oxygen atoms on the phosphonic acid groups. + Mg² + Forming stable multidentate chelates, free Ca²⁺ + / Mg² + The concentration is reduced below the critical value required for silicate precipitation, thereby blocking the formation of insoluble silicate precipitates at the source. The wetting agent reduces the surface tension of the etching solution and improves the wetting and penetration ability of the etching solution to the laser-modified micropores. The alkanolamine additive provides auxiliary chelation, wetting and penetration and pH buffering functions. The synergistic effect of the components enables the alkaline etching solution to achieve through-hole formation of soda-lime glass with a thickness of 1.1 mm or less. That is, through-hole formation is achieved in a single etching based on the continuous laser modification route. The etching rate is high, there is no precipitation blockage, and the hole wall is smooth.
[0010] Thirdly, embodiments of this application provide a soda-lime glass with through holes, wherein the through holes are made using the soda-lime glass through-hole processing method described in the above embodiments.
[0011] The sodium-calcium glass with through holes obtained in this application embodiment is fabricated using the aforementioned sodium-calcium glass through-hole processing method. In this method, the polyamino and polyphosphonic acid chelating agents contained in the alkaline etching solution react with Ca²⁺ released during the etching process through multiple amino and phosphonic acid groups in the molecule. + Mg² + The formation of stable multidentate chelates blocks the formation of insoluble silicate precipitates at the source. At the same time, the wetting agent and alkanolamine additives work together to reduce surface tension and improve the uniformity of mass transfer within the micropores. Combined with optimized stirring and air introduction conditions, the vias remain unobstructed and do not shrink during the etching process. This results in high-quality vias with high aspect ratio, low wall roughness, no deposits, and no hazy surface, meeting the stringent requirements of high-end TGV metallization for hole wall flatness. Attached Figure Description
[0012] The accompanying drawings described below are merely some embodiments of this application. Those skilled in the art can obtain other drawings based on these drawings without any creative effort.
[0013] Figure 1 This is an enlarged cross-sectional view of the soda-lime glass substrate of Embodiment 1 of this application. Detailed Implementation
[0014] To make the technical problems, technical solutions, and beneficial effects of this application clearer, the following detailed description is provided in conjunction with embodiments. It should be understood that the specific embodiments described herein are merely illustrative and not intended to limit the scope of this application.
[0015] In this application, the term "and / or" describes the relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, A and B existing simultaneously, or B existing alone. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0016] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0017] It should be understood that in the various embodiments of this application, the order of the above processes does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0018] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms “a,” “the,” and “the” used in the embodiments of this application and the appended claims are also intended to include the plural forms unless the context clearly indicates otherwise.
[0019] The weights of the relevant components mentioned in the embodiments of this application can refer not only to the specific content of each component, but also to the proportional relationship between the weights of the components. Therefore, any scaling up or down of the content of the relevant components according to the embodiments of this application is within the scope disclosed in the embodiments of this application. Specifically, the mass described in the embodiments of this application can be a well-known unit of mass in the chemical industry, such as µg, mg, g, or kg.
[0020] The first aspect of this application provides a method for processing through-holes in soda-lime glass, comprising the following steps: S10: Laser modification is performed on the target area of the soda-lime glass to form a modified area that penetrates the soda-lime glass; S20: The modified area is etched using an alkaline etching solution to form a through hole; The alkaline etching solution is composed of inorganic strong base, chelating agent, wetting agent, alkanolamine agent and water; the chelating agent includes polyamino polyphosphonic acid chelating agent and / or its salt chelating agent containing at least two amino groups and at least two phosphonic acid groups, used to inhibit the formation of precipitates in the through holes.
[0021] The alkaline etching solution of this application embodiment does not contain carboxylic acid complexing agents. In the alkaline etching solution composed of a chelating aid (a polyamino-polyphosphonic acid chelating aid containing at least two amino groups and at least two phosphonic acid groups and / or its salt chelating aid), an inorganic strong base, a wetting agent, and an alkanolamine aid, the multiple amino and phosphonic acid groups in the chelating aid molecule react with the Ca²⁺ released from the soda-lime glass. + Mg² + It forms a stable, soluble, multidentate chelate, thus blocking the Ca²⁺ ionization at its source. + / Mg² + The pathway involves combining with silicate ions to form insoluble silicate precipitates. Meanwhile, the alkanolamine additives also have the functions of assisting chelation, wetting and penetration, and pH buffering. Together with the wetting agent, they reduce the surface tension of the etching solution and improve the mass transfer uniformity in the high aspect ratio micropores. This enables the direct passage of soda-lime glass with a thickness of 1.1 mm or less under alkaline conditions. The etching rate is effectively improved compared with traditional alkaline solutions. The roughness of the inner wall of the through hole is low and there is no precipitation blockage, which significantly improves the efficiency and yield of TGV processing.
[0022] In this embodiment of the application, step S10: laser modification is performed on the target area of the soda-lime glass to form a modified area that penetrates the soda-lime glass.
[0023] In some implementations, the laser used for laser modification of the target area of the soda-lime glass in step S10 includes a picosecond laser or a femtosecond laser.
[0024] Picosecond / femtosecond lasers have extremely short pulse widths and thermal diffusion times that are much shorter than thermal conduction times. This can suppress the expansion of the heat-affected zone to the greatest extent, thereby forming continuous, uniform, and clearly defined modified channels inside the soda-lime glass. At the same time, it effectively avoids the formation of microcracks or thermal stress damage in the modified area, thus preserving the integrity of the microstructure of the modified area. This provides a highly consistent starting interface for the subsequent selective etching of the etching solution along the modified channels, thereby significantly improving etching uniformity and through-hole forming accuracy.
[0025] In some embodiments, the laser pulse width used for laser modification of the target area of soda-lime glass is 800 fs to 5 ps, for example, any one value or a range between any two values from 800 fs, 900 fs, 1 ps, 1.2 ps, 1.5 ps, 1.8 ps, 2 ps, 2.5 ps, 3 ps, 3.5 ps, 4 ps, 4.5 ps, to 5 ps.
[0026] The laser pulse width is controlled between 800 fs and 5 ps, which falls into the category of ultrafast lasers. Its pulse duration is extremely short, much shorter than the thermal diffusion time in the glass material. This allows the laser energy to be absorbed by the modified area and complete the photo-thermal or photo-chemical conversion in a very short time. The heat does not have time to conduct and diffuse to the surrounding unmodified areas, thus controlling the heat-affected zone at the nanoscale. This effectively avoids thermal damage defects such as microcracks, thermal stress, or excessive melting in the modified area, thereby forming continuous, uniform, and structurally complete modified channels inside the glass.
[0027] In some embodiments, the energy of the laser is 50~150μJ, for example, any one value or a range between any two values from 50μJ, 52μJ, 55μJ, 58μJ, 60μJ, 65μJ, 70μJ, 75μJ, 80μJ, 85μJ, 90μJ, 100μJ, 110μJ, 120μJ, 130μJ, 140μJ, and 150μJ.
[0028] In this embodiment, the laser energy is controlled within the range of 50~150μJ. This energy level is sufficient to excite a stable nonlinear absorption effect inside the soda-lime glass, allowing the laser energy to form sufficient energy deposition in the modified region to achieve permanent modification of the glass network structure. However, it is also not so high that the modified region will suffer uncontrollable damage such as microcracks, shattering, or excessive disorder. Within this energy range, the energy density of the laser-glass interaction is at an appropriate level, which can form continuous, uniform, and structurally controllable modified channels inside the glass, while ensuring that the chemical activity of the modified region is moderately improved while the microstructure remains relatively intact.
[0029] In some implementations, the frequency of the laser is 100 to 300 kHz, for example, any one value or a range between any two values from 100 kHz, 110 kHz, 120 kHz, 130 kHz, 150 kHz, 180 kHz, 200 kHz, 230 kHz, 250 kHz, 280 kHz, to 300 kHz.
[0030] In this embodiment, the laser repetition frequency is controlled within the range of 100~300kHz. This frequency ensures that a sufficient number of pulses act on the target area of the soda-lime glass per unit time, so that the modified channel forms a continuous, uniform and dense modified structure in the depth direction, avoiding discontinuous modification or insufficient modification due to too low a frequency. At the same time, this frequency range does not cause excessive heat accumulation between adjacent pulses due to too short pulse intervals, thereby effectively suppressing the expansion of the heat-affected zone and thermal stress damage. This allows the microstructure of the modified area to obtain suitable selective etching activity while maintaining its integrity, providing a structurally continuous and uniformly active modified interface for the subsequent uniform and rapid selective etching of the modified channel by the alkaline etching solution.
[0031] In step S10 of this embodiment, an ultrafast laser (picosecond laser or femtosecond laser) is used to modify the target area of the soda-lime glass. By precisely controlling the laser frequency (100~300kHz), pulse width (500fs~5ps), and energy (50~150μJ), a continuous and interconnected modified microchannel is formed inside the glass. Due to the extremely short pulse width of the ultrafast laser and the extremely small heat-affected zone, the integrity of the microstructure of the modified area can be effectively preserved. This significantly improves the etching selectivity between the modified and unmodified areas, providing a structural basis for the rapid and uniform penetration of the subsequent etching solution along the modified channel, thereby achieving high aspect ratio forming and high consistency of the through hole.
[0032] In this embodiment, S20: the modified area is etched using an alkaline etching solution to form a through hole.
[0033] The alkaline etching solution used in this application utilizes the high concentration of OH- ions generated by the ionization of a strong inorganic base. - As a nucleophile, it preferentially attacks the highly reactive soda-lime glass network modified by ultrafast laser, breaking the Si-O-Si bonds, causing the glass framework to disintegrate and releasing Ca²⁺. + Mg² + Meanwhile, polyamino-polyphosphonic acid chelating agents bind with Ca²⁺ through multiple amino and phosphonic acid groups in their molecules. + Mg² + Forming stable, soluble, multidentate chelates to block Ca²⁺ at its source. + / Mg² +It combines with silicate ions to form insoluble silicate precipitates. With the help of wetting agents to reduce surface tension and promote the penetration of etching solution into micropores with high aspect ratio, and with the assistance of alkanolamine additives to chelate and stabilize pH, it can achieve high-speed, uniform and non-clogging etching of laser-modified areas under high temperature and alkaline conditions.
[0034] In some embodiments, the raw materials of the alkaline etching solution, by mass fraction, include the following components: Inorganic strong bases 10~40%, for example, any one value or any range between two values from 10%, 12%, 14%, 16%, 18%, 20%, 25%, 28%, 30%, 35%, 40%. The chelating agent is 1-3%, for example, any one value or a range between any two values from 1%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, 1.8%, 1.9%, 2%, 2.1%, 2.2%, 2.3%, 2.4%, 2.5%, 2.6%, 2.7%, 2.8%, 2.9%, 3%; optionally, the mass fraction of the chelating agent is 1.8-3%. The wetting agent is 0.1-2%, for example, any one value or a range between any two values from 0.1%, 0.2%, 0.3%, 0.5%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.7%, 1.8%, 1.9%, 2%. Alkylamine auxiliaries, 0.1% to 1%, for example, any one value or a range between any two values from 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, to 1%; Water balance.
[0035] This application uses an inorganic strong base as the main etching agent, and a ternary composite etching agent system is constructed with a very low addition amount (1~3%) of a polyamino polyphosphonic acid chelating agent, a wetting agent (0.1~2%), and an alkanolamine agent (0.1~1%). The chelating agent utilizes multiple amino and phosphonic acid groups in its molecule to react with the Ca²⁺ released from the soda-lime glass. + Mg² + This method achieves highly efficient multidentate chelation, and due to the significant "threshold effect" of this chelation, a very small amount of chelating agent can inhibit the formation of a large amount of precipitate by adsorbing onto the crystal nucleus surface and interfering with crystal growth, rather than being consumed one-to-one according to a stoichiometric ratio. Therefore, only a low addition amount of 1.8~3% is needed to block Ca²⁺ at its source. + / Mg² +It combines with silicate ions to form insoluble silicate precipitates; at the same time, alcohol amine additives (such as triethanolamine) provide auxiliary chelation, wetting and penetration and pH buffering functions, and work synergistically with wetting agents to reduce the surface tension of the etching solution and improve the mass transfer uniformity in high aspect ratio micropores; the components of the above ternary compound system cooperate with each other to effectively suppress the precipitation formation during the etching of soda-lime glass through holes without the need to add additional organic weak bases or carboxylic acid complexing agents, and make the etching rate significantly higher than that of traditional alkaline solutions, and the inner wall of the through holes smooth and unblocked.
[0036] In some embodiments, the inorganic strong base includes sodium hydroxide and / or potassium hydroxide.
[0037] In this application, sodium hydroxide and / or potassium hydroxide are used as strong inorganic bases, which can completely ionize in aqueous solution to produce a high concentration of OH-. - The presence of ions provides ample and efficient active groups for the etching reaction of soda-lime glass, ensuring that the Si-O-Si bonds in the glass network are quickly broken, allowing the laser-modified areas to preferentially dissolve and form through-holes. Compared to weak organic bases or low-concentration alkaline solutions, sodium hydroxide / potassium hydroxide provides high OH- ions, thus providing sufficient and efficient active groups for the etching reaction of soda-lime glass, ensuring that the Si-O-Si bonds in the glass network are broken quickly, allowing the laser-modified areas to dissolve preferentially and form through-holes. - The high concentration and high ionic strength environment significantly improve the etching rate and create a favorable solution chemical environment for the stable chelation of polyaminopolyphosphonic acid chelating agents under high temperature and alkaline conditions, thereby synergistically improving the etching efficiency and uniformity of through holes.
[0038] In some embodiments, the polyaminopolyphosphonic acid chelating agent includes one or more of ethylenediaminetetramethylenephosphonic acid (EDTMPA), diethylenetriaminepentamethylenephosphonic acid (DTPMPA), polyaminopolyethermethylenephosphonic acid (PAPEMP), and hexamethylenediaminetetramethylenephosphonic acid (HDTMP). Corresponding polyaminopolyphosphonate chelating agents include sodium salts, potassium salts, etc., such as sodium ethylenediaminetetramethylenephosphonate (EDTMPAS), sodium diethylenetriaminepentamethylenephosphonate, sodium polyaminopolyethermethylenephosphonate, and sodium hexamethylenediaminetetramethylenephosphonate.
[0039] In this application, ethylenediaminetetramethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, polyaminopolyethermethylenephosphonic acid, or hexamethylenediaminetetramethylenephosphonic acid are used as polyaminopolyphosphonic acid chelating agents. These compounds all contain at least two amino groups and at least two phosphonic acid groups, enabling them to react with Ca²⁺ released during the etching process of soda-lime glass through nitrogen atoms and oxygen atoms on the phosphonic acid groups. + Mg² + Forming stable multidentate chelates, free Ca²⁺ + / Mg² +The concentration is reduced to below the critical value required for silicate precipitation, thereby blocking the formation of insoluble silicate precipitates at the source, preventing the modified micropores from being blocked, and achieving unobstructed pores with smooth pore walls and no deposition.
[0040] In some embodiments, the wetting agent includes alkyl glycoside nonionic surfactants and / or polyoxyethylene ether nonionic surfactants.
[0041] In this application, alkyl glycoside nonionic surfactants and / or polyoxyethylene ether nonionic surfactants are used as wetting agents. These substances can significantly reduce the surface tension of alkaline etching solutions, improve the wetting and penetration ability of the etching solution on the inner wall of laser-modified micropores, and enable the etching solution to quickly and uniformly enter the depth of micropores with high aspect ratios. This ensures a uniform concentration distribution of the etching solution in the channel and timely diffusion of reaction products, thereby avoiding precipitation caused by local oversaturation. At the same time, combined with the low foaming characteristics and high temperature stability of the nonionic surfactants themselves, the etching process is ensured to be uniform and controllable, resulting in high-quality through-hole formation and smooth, flat hole walls.
[0042] In some embodiments, the alkyl glycoside nonionic surfactant includes C8-C14 alkyl glucosides and / or isomeric alcohol alkyl glycosides.
[0043] In this application, C8-C14 alkyl glucosides and / or isomeric alcohol alkyl glycosides are selected as alkyl glycoside nonionic surfactants. C8-C14 alkyl glucosides have a moderate hydrophilic-lipophilic balance and good biodegradability, which can effectively reduce the surface tension of the etching solution and promote the uniform spreading and penetration of the etching solution in the laser-modified micropores. Isomeric alcohol alkyl glycosides, due to their branched alkyl structure, exhibit excellent solubility and wettability in a strongly alkaline environment, and their characteristic of "increasing wettability with increasing alkalinity" further enhances the penetration ability of the etching solution into micropores with high aspect ratio. When used alone or in combination, both can work synergistically with chelating agents and alkanolamine agents to ensure that the etching solution stably wets the inner wall of the pores under alkaline conditions, promotes the timely diffusion and discharge of reaction products, and thus avoids precipitation caused by local supersaturation.
[0044] In some embodiments, C8-C14 alkyl glucosides include one or more of octyl-decyl glucoside, decyl glucoside, lauryl glucoside, and myristyl glucoside, which can be adapted to high-concentration, strong-alkali, and high-temperature environments and have excellent wetting and penetration.
[0045] In some embodiments, the wetting agent includes alkyl glycoside nonionic surfactants and polyoxyethylene ether nonionic surfactants, and the mass fraction of the wetting agent is 0.5-2%.
[0046] In this application embodiment, 0.5-2% of alkyl glycoside nonionic surfactants and polyoxyethylene ether nonionic surfactants are combined as wetting agents. The combination of the two can produce a synergistic effect: alkyl glycosides provide excellent wetting and penetration capabilities and low foaming characteristics, while polyoxyethylene ethers further reduce surface tension and enhance the stability of the etching solution under high temperature and alkaline conditions. The combined effect of the two significantly reduces the surface tension of the etching solution, thereby ensuring that the etching solution can quickly and uniformly penetrate into the depth of the high aspect ratio micropores formed by laser modification, promoting the timely diffusion and discharge of reaction products in the channels, avoiding precipitation caused by local oversaturation. At the same time, the addition of 0.5-2% can fully exert the synergistic wetting effect without affecting the overall stability of the etching solution or generating unnecessary foam that interferes with the etching uniformity due to excessive amount.
[0047] In some embodiments, the polyoxyethylene ether nonionic surfactant includes one or more of AEO-7, AEO-9, and compound nonionic surfactants containing polyoxyethylene ether.
[0048] In this application embodiment, AEO-7, AEO-9, and a compound nonionic surfactant containing polyoxyethylene ether are selected as polyoxyethylene ether wetting agents. Among them, AEO-7 (EO number about 7) has lower surface tension and stronger wetting and penetration ability, which is especially suitable for the scenario where alkaline etching solution can quickly enter micropores with high aspect ratio. AEO-9 (EO number about 9) has a longer hydrophilic chain and a higher cloud point, and has better solubility and stability under alkaline conditions, which can effectively avoid precipitation or deactivation caused by temperature rise. By compounding AEO-7 with AEO-9 or using it with a compound surfactant containing polyoxyethylene ether, a synergistic effect can be produced. While significantly reducing the surface tension of alkaline etching solution, it can improve high-temperature stability, so that alkaline etching solution can maintain excellent wetting and penetration performance throughout the entire through-hole etching process. This ensures that alkaline etching solution is evenly spread on the inner wall of the laser modified micropore, promotes the timely diffusion and discharge of reaction products, and avoids precipitation caused by local supersaturation.
[0049] In some embodiments, the alkanolamine adjuvant includes one or more of monoethanolamine, diethanolamine, triethanolamine, methyldiethanolamine, and diisopropanolamine.
[0050] Monoethanolamine, diethanolamine, triethanolamine, methyldiethanolamine, or diisopropanolamine are selected as amine additives. These amine compounds contain both amino and hydroxyl groups in their molecules, enabling them to exert multiple synergistic effects: the lone pair electrons on their amino groups can interact with the Ca²⁺ released during the etching process of soda-lime glass. + Mg² + It forms an auxiliary coordination bond, which together with the main chelating agent constitutes a dual chelation guarantee, further reducing free Ca²⁺. + / Mg²+ Concentration; its hydroxyl groups can reduce the surface tension of alkaline etching solutions and enhance the wetting and penetration ability of alkaline etching solutions for laser-modified micropores; at the same time, as a weak base, the alcohol amine additive can act as a pH buffer during the etching process, stabilizing OH groups. - Concentration is controlled to avoid uneven etching rates caused by local pH fluctuations. Through the triple functions of auxiliary chelation, wetting and penetration, and pH buffering, the amine-based additives work synergistically with the chelating additives and wetting agents to ensure a uniform and stable etching process, resulting in through-holes with smooth, deposit-free walls.
[0051] In some embodiments, the modified region is etched using an alkaline etching solution, including: immersing the laser-modified soda-lime glass in the alkaline etching solution, introducing air into the alkaline etching solution, controlling the temperature of the alkaline etching solution to 70-110°C, and etching the soda-lime glass under stirring conditions. The temperature of the alkaline etching solution is 70-110°C, for example, any single value or a range between any two values from 70°C, 72°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C, 105°C, and 110°C.
[0052] In this embodiment, during the etching process, laser-modified soda-lime glass is immersed in an alkaline etching solution, and air is introduced into the solution. The etching solution temperature is controlled at 70-110°C, and etching is performed under stirring conditions. The microbubbles formed by the introduced air are uniformly dispersed in the etching solution under stirring. The rising and bursting of these microbubbles generate local turbulence and micro-disturbances, effectively promoting the circulation and timely removal of reaction products within the laser-modified micropores, preventing local ion oversaturation within the channels. The high temperature of 70-110°C significantly increases the etching reaction rate, causing the modified areas to dissolve rapidly, thus achieving through-hole connectivity. The combined effect of stirring and microbubbles ensures a uniform distribution of temperature and concentration in the alkaline etching solution, avoiding inconsistent hole shapes or precipitation caused by local differences, thereby improving through-hole consistency, aspect ratio, and hole wall smoothness.
[0053] In some implementations, the airflow rate is 0.3 to 1.0 L / min, for example, any one value or a range between any two values from 0.3 L / min, 0.4 L / min, 0.5 L / min, 0.6 L / min, 0.7 L / min, 0.8 L / min, 0.9 L / min, and 1 L / min.
[0054] In this embodiment, during the etching process, laser-modified soda-lime glass is immersed in an alkaline etching solution, and air is introduced into the solution at a flow rate of 0.3~1.0 L / min. Etching is performed simultaneously under stirring conditions at 70~110°C. This specific air flow rate range enables the formation of moderately dense and stable microbubbles in the etching solution. The rising and bursting of these microbubbles, under stirring, generates continuous local turbulence and micro-disturbances, effectively promoting the circulation and renewal of the etching solution within the high aspect ratio laser-modified micropores and the reaction products within the channels (such as chelated Ca²⁺). + / Mg² + The timely removal of complexes and dissolved silicates prevents precipitation due to local ion supersaturation in the channels, while avoiding excessively large or dense bubbles that could block the channel entrance or cause uneven etching. Combined with high-temperature conditions of 70~110℃ and stirring, this airflow range ensures that the temperature and concentration of the etching solution are uniformly distributed throughout the entire glass substrate, thereby improving the etching rate, via consistency, aspect ratio, and hole wall smoothness.
[0055] In some embodiments, the air flow rate is 0.3~1.0L / min and the stirring speed is 400~1000rpm / min.
[0056] In this embodiment, during the etching process, laser-modified soda-lime glass is immersed in an alkaline etching solution. The air flow rate is controlled at 0.3~1.0 L / min, the stirring speed at 400~1000 rpm / min, and the etching is performed at 70~110℃. This specific range of air flow rate and stirring speed works together to form a moderate and stable microbubble turbulence field in the etching solution. The rise and collapse of microbubbles generate continuous local micro-disturbances under the stirring action, while forced convection ensures that the etching solution circulates and renews rapidly within the high aspect ratio laser-modified micropores. Both work synergistically to promote the reaction products (such as chelated Ca²⁺) within the channels. + / Mg² + The timely diffusion and discharge of complexes and dissolved silicates effectively prevents precipitation due to local ion supersaturation in the pores. At the same time, this parameter range avoids insufficient mass transfer caused by excessively dense bubbles or slow stirring, as well as excessive scouring or uneven etching at the pore inlet caused by excessively large bubbles or fast stirring. Combined with the high temperature conditions of 70~110℃, the synergistic effect of the air flow rate and stirring speed can ensure that the temperature and concentration of the etching solution are uniformly distributed throughout the entire glass substrate.
[0057] The second aspect of this application provides an alkaline etching solution for processing through-holes in soda-lime glass, applied to the soda-lime glass through-hole processing method described in the above embodiments. The raw materials of the alkaline etching solution for processing through-holes in soda-lime glass include an inorganic strong alkali, a chelating agent, a wetting agent, an alkanolamine agent, and water. The chelating agent includes polyamino polyphosphonic acid chelating agents and / or their salts containing at least two amino groups and at least two phosphonic acid groups.
[0058] The alkaline etching solution in this embodiment does not contain carboxylic acid complexing agents, but instead uses an inorganic strong base as the main etching agent, providing a high concentration of OH-. - The ions efficiently disrupt the Si-O-Si network framework of soda-lime glass. Simultaneously, the core functional components are polyamino-polyphosphonic acid chelating agents and / or their salts. The molecules contain at least two amino groups and at least two phosphonic acid groups, enabling them to interact with the Ca²⁺ released during the etching process of soda-lime glass through nitrogen atoms and oxygen atoms on the phosphonic acid groups. + Mg² + Forming stable multidentate chelates, free Ca²⁺ + / Mg² + The concentration is reduced below the critical value required for silicate precipitation, thereby blocking the formation of insoluble silicate precipitates at the source. The wetting agent reduces the surface tension of the etching solution and improves the wetting and penetration ability of the etching solution to laser-modified micropores. The alkanolamine additive provides auxiliary chelation, wetting and penetration and pH buffering functions. The synergistic effect of the components enables the etching solution to achieve direct penetration of soda-lime glass with a thickness of 1.1 mm and below under high temperature and alkaline conditions. The etching rate is high, there is no precipitation blockage, and the pore walls are smooth.
[0059] The specific composition of the alkaline etching solution in this application embodiment is as described in the sodium-calcium glass through-hole processing method in the above embodiment, and will not be repeated here.
[0060] The third aspect of this application provides a soda-lime glass with through holes, wherein the through holes are made using the soda-lime glass through-hole processing method described in the above embodiments.
[0061] The sodium-calcium glass with through holes obtained in this application embodiment is fabricated using the aforementioned sodium-calcium glass through-hole processing method. In this method, the polyamino and polyphosphonic acid chelating agents contained in the alkaline etching solution react with Ca²⁺ released during the etching process through multiple amino and phosphonic acid groups in the molecule. + Mg² +The formation of stable multidentate chelates blocks the formation of insoluble silicate precipitates at the source. At the same time, the wetting agent and alkanolamine additives work together to reduce surface tension and improve the uniformity of mass transfer within the micropores. Combined with optimized stirring and air introduction conditions, the vias remain unobstructed and do not shrink during the etching process. This results in high-quality vias with high aspect ratio, smooth walls, no deposits, and no haze, meeting the stringent requirements for hole wall flatness in high-end TGV metallization.
[0062] In some embodiments, the depth-to-diameter ratio of the through hole is ≥80:1 and ≤150:1, for example, any one value or a range between any two values of 80:1, 82:1, 85:1, 88:1, 90:1, 92:1, 95:1, 100:1, 110:1, 120:1, 130:1, 140:1, 150:1; the inner wall roughness of the through hole is ≤50nm, for example, any one value or a range between any two values of 10nm, 15nm, 20nm, 25nm, 30nm, 33nm, 35nm, 37nm, 40nm, 43nm, 45nm, 48nm, 50nm.
[0063] Because polyamino-polyphosphonic acid chelating agents bind with Ca released during etching through multiple amino and phosphonic acid groups in their molecules... 2+ Mg 2+ The formation of stable, soluble, multidentate chelates blocks the formation of insoluble silicate precipitates at the source, preventing the modified micropores from being blocked or shrinking during etching. This allows the etching solution to continuously and effectively perform uniform etching along the entire length of the modified channel. At the same time, the wetting agent reduces the surface tension of the etching solution, improves the wetting and penetration of the inner wall of the high aspect ratio micropores, and facilitates the timely discharge of reaction products. This ensures that all parts of the channel inner wall maintain fresh etching solution contact and a uniform etching rate during the etching process. As a result, while achieving high-density vertical interconnects with aspect ratios ≥80:1 and ≤150:1, ultra-smooth hole walls with an inner wall roughness ≤50nm are obtained, meeting the stringent requirements of high aspect ratio and low roughness for high-end TGV packaging.
[0064] The embodiments of this application are described in detail below. The embodiments described below are exemplary and are only used to explain this application, and should not be construed as limiting this application. Where specific techniques or conditions are not specified in the embodiments, they are performed in accordance with the techniques or conditions described in the literature in this field or according to the product instructions. Reagents or instruments used, unless otherwise specified, are all conventional products that can be obtained commercially.
[0065] Example 1 Preparation of alkaline etching solution: Mix the raw materials as follows: potassium hydroxide: 32wt%, EDTMPS (ethylenediaminetetramethylenephosphonate sodium): 2wt%, lauryl glucoside: 0.2wt%, triethanolamine: 0.5wt%, and deionized water: 65.3wt%.
[0066] Laser modification: An infrared laser with a frequency of 100kHz, a pulse width of 1000fs, and an energy of 100μJ is used to modify the target area of a 1.1mm thick soda-lime glass substrate, forming a modified area that penetrates the soda-lime glass substrate. Etching: The laser-modified 1.1mm thick soda-lime glass substrate is immersed in an alkaline etching solution and kept at a constant temperature of 85℃. Air is introduced into the alkaline etching solution (flow rate of 0.3L / min) to keep the alkaline etching solution in a micro-bubbling state. The soda-lime glass substrate is etched at a stirring speed of 1000rpm / min to form through holes.
[0067] Post-processing: The substrate is rinsed with deionized water and then ultrasonically cleaned to remove any residue from the surface of the soda-lime glass substrate.
[0068] Example 2 This embodiment is basically the same as Example 1, except that the composition of the alkaline etching solution is as follows: potassium hydroxide: 20.0 wt%, sodium hydroxide: 15.0 wt%, EDTMPA: 2.2 wt%, JFC-M: 0.4 wt%, triethanolamine: 1.0 wt%, and deionized water as the balance.
[0069] Example 3 This embodiment is basically the same as Example 1, except that the composition of the alkaline etching solution is as follows: potassium hydroxide: 30.0 wt%, EDTMPS: 1.8 wt%, APG0810: 0.3 wt%, triethanolamine: 0.3 wt%, and deionized water as the balance.
[0070] Example 4 This embodiment is basically the same as Example 1, except that the composition of the alkaline etching solution is as follows: potassium hydroxide: 10.0 wt%, EDTMPS: 1.8 wt%, APG0810: 0.1 wt%, triethanolamine: 0.1 wt%, and deionized water as the balance.
[0071] Example 5 This embodiment is basically the same as Example 1, except that the composition of the alkaline etching solution is as follows: potassium hydroxide: 40.0 wt%, EDTMPS: 3 wt%, AEO-7: 1 wt%, APG0810: 1 wt%, diethanolamine: 1 wt%, and deionized water as the balance.
[0072] Example 6 This embodiment is basically the same as Embodiment 1, except that: Infrared laser parameters: frequency 300kHz, pulse width 4ps, energy 150μJ.
[0073] Etching conditions: constant temperature of 105℃, air flow rate of 1L / min, stirring speed of 400rpm / min.
[0074] Example 7 This embodiment is basically the same as Embodiment 1, except that: Infrared laser parameters: frequency 200kHz, pulse width 5ps, energy 120μJ.
[0075] Etching conditions: constant temperature of 70℃, air flow rate of 0.6L / min, and stirring speed of 600rpm / min.
[0076] Example 8 This embodiment is basically the same as that of embodiment 1, except that the amount of EDTMPS in the alkaline etching solution in embodiment 1 is adjusted to 1 wt.
[0077] Example 9 This embodiment is basically the same as that of embodiment 1, except that the amount of EDTMPS in the alkaline etching solution in embodiment 1 is adjusted to 1.2wt%.
[0078] Example 10 This embodiment is basically the same as that of embodiment 1, except that the amount of EDTMPS in the alkaline etching solution in embodiment 1 is adjusted to 1.5wt.
[0079] Example 11 This embodiment is basically the same as that of embodiment 1, except that the amount of EDTMPS in the alkaline etching solution in embodiment 1 is adjusted to 3.5wt%.
[0080] Example 12 This embodiment is basically the same as Embodiment 1, except for the infrared laser parameters: frequency 80kHz, pulse width 1000fs, energy 100μJ.
[0081] Example 13 This embodiment is basically the same as Embodiment 1, except for the infrared laser parameters: frequency 400kHz, pulse width 1000fs, energy 150μJ.
[0082] Example 14 This embodiment is basically the same as Embodiment 1, except for the infrared laser parameters: frequency 100kHz, pulse width 800fs, energy 150μJ.
[0083] Example 15 This embodiment is basically the same as Embodiment 1, except for the infrared laser parameters: frequency 100kHz, pulse width 5ps, energy 150μJ.
[0084] Example 16 This embodiment is basically the same as Embodiment 1, except for the infrared laser parameters: frequency 100kHz, pulse width 1000fs, energy 40μJ.
[0085] Example 17 This embodiment is basically the same as Embodiment 1, except for the infrared laser parameters: frequency 100kHz, pulse width 1000fs, energy 200μJ.
[0086] Example 18 This embodiment is basically the same as Embodiment 1, except that no air is allowed in the alkaline etching solution during the etching process.
[0087] Example 19 This embodiment is basically the same as Example 1, except that the composition of the alkaline etching solution is as follows: sodium hydroxide: 32wt%, EDTMPS: 2wt%, lauryl glucoside: 0.2wt%, triethanolamine: 0.5wt%, deionized water: 65.3wt%.
[0088] Example 20 This embodiment is basically the same as Embodiment 1, except that a 0.5mm thick soda-lime glass substrate is used. The laser modification parameters are adjusted to: frequency 150kHz, pulse width 800fs, and energy 80μJ.
[0089] Comparative Example 1 This comparative example is basically the same as Example 1, except that the alkaline etching solution in Example 1 is replaced with an acidic etching solution: HF: 2.5wt%, NH4F: 20wt%, EDTMPS: 2wt%, lauryl glucoside: 0.2wt%, triethanolamine: 0.3wt%, and deionized water as the balance.
[0090] Comparative Example 2 This comparative example is basically the same as Example 1, except that EDTMPS in Example 1 is replaced with diethylenetriaminepentaacetic acid (a carboxylic acid chelating agent).
[0091] Comparative Example 3 This comparative example is basically the same as Example 1, except that EDTMPS in Example 1 is replaced with gluconic acid (a polyhydroxy organic chelating agent).
[0092] Comparative Example 4 This comparative example is basically the same as Example 1, except that the alkaline etching solution is as follows: potassium hydroxide: 32wt%, cyclohexanediaminetetraacetic acid: 0.34wt%, ethylenediaminetetramethylenephosphonic acid: 0.28wt%, 5,5'-dimethyl-2,2'-bipyridine: 1.29wt%, gluconic acid: 0.09wt%, lauryl glucoside: 0.2wt%, triethanolamine: 0.5wt%, and deionized water as the balance.
[0093] Comparative Example 5 This comparative example is basically the same as Example 1, except that the EDTMPS in the alkaline etching solution of Example 1 is replaced with an equal amount of aminotrimethylphosphonic acid.
[0094] Comparative Example 6 This comparative example is basically the same as Example 1, except that the EDTMPS in the alkaline etching solution of Example 1 is replaced with an equal amount of sodium ethylenediamine disuccinate.
[0095] Comparative Example 7 This comparative example is basically the same as Example 1, except that the EDTMPS in the alkaline etching solution of Example 1 is replaced with an equal amount of sodium ethylenediaminetetraacetate.
[0096] Comparative Example 8 This comparative example is basically the same as Example 1, except that the triethanolamine in the alkaline etching solution of Example 1 is replaced with an equal amount of dimethylamine.
[0097] Comparative Example 9 This comparative example is basically the same as Example 1, except that triethanolamine is not added to the alkaline etching solution in Example 1 (the remaining amount is made up with deionized water).
[0098] Comparative Example 10 This comparative example is basically the same as Example 1, except that EDTMPS is not added to the alkaline etching solution in Example 1 (the remaining amount is made up with deionized water).
[0099] Comparative Example 11 This comparative example is basically the same as Example 1, except that lauryl glucoside is not added to the alkaline etching solution in Example 1 (the remaining amount is made up with deionized water).
[0100] Comparative Example 12 This comparative example is basically the same as Example 1, except that lauryl glucoside in the alkaline etching solution of Example 1 is replaced with an equal amount of hexadecyltrimethylammonium bromide.
[0101] Test case The through-hole processing results of Examples 1-20 and Comparative Examples 1-12 are shown in Table 1. Among them, the through-hole straightness effect after processing in Example 1 is as follows: Figure 1 As shown.
[0102] Etching rate: Measure the thickness before and after etching, calculate the thickness difference before and after etching, and divide the thickness difference by the etching time to get the etching rate.
[0103] Roughness: Tested according to standard ISO 4287, i.e., the glass is cut along TGV and the arithmetic mean roughness Ra of the inner wall of the middle section is measured.
[0104] Aspect ratio: The effective depth of the through hole (the depth of the through hole is the thickness of the soda-lime glass substrate) divided by the diameter of the hole at the center position of the through hole in the axial direction.
[0105] Table 1
[0106] Replacing the alkaline etching solution in Example 1 of this application with an acidic etching solution based on hydrofluoric acid, primarily HF and supplemented by NH4F and inorganic acids (Comparative Example 1), significantly improved the etching rate. However, the etching process generated a large amount of fluoride precipitate, forming a white film on the surface that blocked the modified micropores. This resulted in poor taper of the through-holes, severe lateral etching, and surface defects such as a hazy finish. The high roughness of the inner wall prevented the processing of high aspect ratio through-holes in 1.1mm thick soda-lime glass. This is because EDTMPS in Comparative Example 1 could not exert its chelating effect in the HF / NH4F acidic system. Specifically, in an acidic environment with a pH of approximately 3-4, the phosphonic acid groups (-PO3²) of EDTMPS... - It is protonated to the -PO3H2 form, losing its affinity for Ca²⁺. + The coordination ability of HF is limited; however, fluorination side reactions may occur between HF and phosphonic acid groups, further disrupting the molecular structure of EDTMPS. Therefore, this comparative example verifies that polyaminopolyphosphonic acid chelating agents can only fully exert their precipitation-inhibiting function under alkaline conditions.
[0107] When the EDTMPS (chelating agent) in the alkaline etching solution of Example 1 of this application is replaced with diethylenetriaminepentaacetic acid (Comparative Example 2), the carboxylic acid-Ca²⁺ is subjected to strong alkaline high temperature at 85°C. + The coordination bonds are mainly ionic, which have poor thermal stability and break and become inactive; at the same time, DTPA undergoes decarboxylation degradation and cannot effectively chelate Ca²⁺. + / Mg² + A large amount of precipitate blocked the pores. Therefore, this comparative example verifies that the phosphonic acid group cannot be replaced by a carboxylic acid.
[0108] When the EDTMPS (chelating agent) in the alkaline etching solution of Example 1 of this application was replaced with gluconic acid (Comparative Example 3), the etching rate was only 1 μm / h, a small amount of precipitation appeared, the through-hole depth-to-diameter ratio was only 33:1, and the inner wall roughness was as high as 98 nm. This is because the chelating stability constant of gluconic acid is logK≈2.5, which is only a few hundredths of that of EDTMPS (logK≈8~10); and it undergoes alkaline degradation in a strong alkali at 85°C. Because it completely lacks amino groups and has no nitrogen atoms for coordination, its chelating ability is extremely weak. Therefore, polyhydroxycarboxylic acid organic compounds have a very weak chelating ability in a high-temperature alkaline system for Ca²⁺. + / Mg² + The chelating ability is far from sufficient to meet the requirements for inhibiting precipitation during the processing of soda-lime glass (TGV).
[0109] Comparative Example 4, based on Example 1 of this application, modified the alkaline etching solution formulation (i.e., simulated a multi-component metal complexation control agent system, using cyclohexanediaminetetraacetic acid 0.34 wt%, EDTMPA 0.28 wt%, 5,5′-dimethyl-2,2′-bipyridine 1.29 wt%, and gluconic acid 0.09 wt% as the chelating system). The etching rate was only 0.8 μm / h, and a large amount of metal salt precipitate was generated on the inner wall of the through-hole, making it impossible to achieve through-holes. This is because EDTMPA was only 0.28 wt% (far lower than the 2 wt% in Example 1), and bipyridine is a hydrophobic bipyridine ligand, which is insoluble in alkaline solutions. The carboxylic acids and gluconic acid had insufficient chelating ability under high temperature and alkaline conditions, and all components were ineffective. This comparative example fully demonstrates that Example 1 of this application, using only a ternary core system of a single main chelating agent (2wt% EDTMPS) of polyamino polyphosphonic acid chelating adjuvant combined with a wetting agent and an alcohol amine adjuvant, can achieve technical effects far superior to complex quaternary chelating systems with multiple components and low single concentrations. This reflects the significant advantages of the technical solution of this application in terms of component simplification, high efficiency and excellent effect.
[0110] When the EDTMPS in the alkaline etching solution of Example 1 of this application was replaced with an equal amount of aminotrimethylphosphonic acid (Comparative Example 5, ATMP), the etching rate was only 1 μm / h, a large amount of precipitation occurred, and through-holes could not be achieved. This is because ATMP contains only one tertiary amine nitrogen atom and three phosphonic acid groups (i.e., stoichiometry of 1N:3P). A single nitrogen atom cannot form a multi-nitrogen cooperative coordination with Ca²⁺. + / Mg² + It can only form tridentate / tetradentate chelates, which are far weaker than the stable hexadentate chelate structure of EDTMPS. Furthermore, its nitrogen atom's coordination ability is further weakened due to the electron-withdrawing effect. This comparative example, from the reverse perspective, verifies the necessity and criticality of the structural limitation of "containing at least two amino groups and at least two phosphonic acid groups" for achieving the technical effects of this application.
[0111] When the EDTMPS in the alkaline etching solution of Example 1 of this application was replaced with an equal amount of sodium ethylenediamine disuccinate (Comparative Example 6), the etching rate was only 1 μm / h, and a large amount of silicate flocculent precipitate appeared on the glass surface and inside the holes, making it impossible to achieve through-holes. Although EDTMPS and sodium ethylenediamine disuccinate (EDDS) both have an ethylenediamine core (2N:4 coordination group), the coordination functional group is a carboxylate group, and its PO-Ca phosphonic acid covalent bond is changed to -COO. - -Ca² + Ionic bonds result in an effective stability constant that is 4-6 orders of magnitude lower at high temperatures. This comparative example illustrates that even with the same molecular skeleton (ethylenediamine core) and number of coordinating atoms, the chemical properties of the coordinating functional groups (phosphonic acid groups vs. carboxylic acid groups) are what determine the chelating agent's effect on Ca²⁺ under high-temperature alkaline conditions. + / Mg² + The key factors for chelation effect verify the irreplaceable nature of the polyaminopolyphosphonic acid chelating agent selected in this application.
[0112] When the alkaline etching solution of Example 1 of this application was replaced with an equal amount of sodium ethylenediaminetetraacetate (Comparative Example 7, EDTA-4Na), the etching rate was 3 μm / h, the aspect ratio was only 37:1, silicate flocculent precipitates appeared on the glass surface and inside the holes, and the roughness of the inner wall of the through holes reached as high as 78 nm. This is because although the chelating ability of EDTA-4Na at room temperature is comparable to that of EDTMPS, the carboxylic acid-Ca²⁺ chelating ability at 85°C is significantly higher. + Coordination bonds break and recombine frequently due to thermal motion, shortening the effective chelation time and partially depleting Ca²⁺. + In the gaps between the broken coordination bonds, it combines with silicate ions in the solution to form a precipitate. Furthermore, the conjugate acidity of the phosphonic acid group in EDTMPS (pKa2≈7.1~7.7) is much weaker than that of the carboxylic acid in the EDTA molecule (pKa≈4~5). Under strongly alkaline conditions, the phosphonic acid group transforms into a -PO3² group carrying two negative charges. - In this form, the anion charge density is higher, similar to Ca²⁺. + The electrostatic attraction is stronger. Furthermore, EDTA has only 6 coordination sites (vs. EDTMPS 10), resulting in a less dense coordination layer and a significant performance difference. This indicates that carboxylic acid chelating agents have some effect under high-temperature alkaline TGV conditions, but cannot achieve the superior performance level achieved by the polyaminopolyphosphonic acid chelating agent of this application.
[0113] When the triethanolamine in the alkaline etching solution of Example 1 of this application was replaced with an equal amount of dimethylamine (Comparative Example 8), the etching rate decreased to 4 μm / h, the inner wall roughness was 68 nm, the aspect ratio was 90:1, and etching solution stratification and localized intensified lateral corrosion occurred. This is because dimethylamine lacks hydroxyl groups and therefore has no wetting function (poor microporous solution displacement), its pKa≈10.7 provides no buffering capacity in strong alkali (uneven lateral corrosion), and its boiling point is only 7°C, resulting in significant volatilization at high temperatures (solution stratification). This comparative example verifies that the auxiliary chelation, wetting, and buffering functions of amine-based additives are indispensable.
[0114] When triethanolamine was not added to the alkaline etching solution of Example 1 of this application (Comparative Example 9), the etching rate decreased to 3.5 μm / h, the roughness was 77 nm, and the aspect ratio decreased to 82:1. Etching solution stratification, poor micropore solution replacement, and increased localized lateral corrosion occurred. This is because Comparative Example 9 did not contain triethanolamine, thus lacking its auxiliary chelating agent (EDTMPS chelate dissociation accelerated, effective stabilization time shortened, and some Ca²⁺...). + / Mg² + Released deep within micropores and combined with silicate ions to form precipitates), pH buffer (OH groups at the pore opening and depth). - The comparative example demonstrates the triple function of gradient runaway leading to increased taper and auxiliary wetting (0.2 wt% lauryl glucoside alone is insufficient to reduce surface tension, causing local supersaturation and hindered mass transfer). This comparative example proves the necessity of alkanolamine auxiliaries as an indispensable third component in the ternary compound system of this application.
[0115] When EDTMPS (Comparative Example 10) was not added to the alkaline etching solution of Example 1 of this application, the etching rate dropped sharply to 0.5 μm / h, resulting in a large amount of precipitate forming and blocking the vias, making it impossible to achieve through-holes. Only KOH etching released Ca²⁺. + / Mg² + Immediately with SiO3² - The reaction produces a sparingly soluble CaSiO3 / MgSiO3 precipitate (Ksp≈10). -8 ), quickly seal the entrance and interior of the modified microchannel, OH - The reaction could not proceed, and the process failed completely. This comparative example demonstrates that during the alkaline TGV processing of soda-lime glass, the effective chelation of Ca²⁺ released during etching is crucial. + / Mg² + It is a necessary prerequisite for etching to proceed, and polyaminopolyphosphonic acid chelating agents are the core functional components that enable this prerequisite.
[0116] When lauryl glucoside was not added to the alkaline etching solution of Example 1 of this application (Comparative Example 11, without wetting agent), although the etching rate remained at 4.5 μm / h and through-holes were achieved (depth-to-diameter ratio 93:1), the inner wall roughness significantly increased to 72 nm (1.95 times that of Example 1), and the poor wettability led to inconsistent pore sizes and deviations in glass thickness in different areas. In Comparative Example 11, without wetting agent, the surface tension was as high as ~70 mN / m, preventing the etching solution from quickly penetrating deep into the high-depth-to-diameter ratio micropores, resulting in a larger inlet pore size and a smaller inner pore size; uneven bubble distribution caused thickness deviations in different areas, poor product discharge from the pores, and localized supersaturation leading to micro-precipitations. This comparative example verifies the key auxiliary role of wetting agents in achieving high through-hole consistency and low roughness in the ternary compound system of this application.
[0117] When lauryl glucoside in the alkaline etching solution of Example 1 of this application was replaced with an equal amount of hexadecyltrimethylammonium bromide (Comparative Example 12, CTAB, cationic surfactant), the etching rate was 4.5 μm / h, achieving through-holes (but the depth-to-diameter ratio was only 55:1, far lower than the 100:1 of Example 1). However, the inner wall roughness was as high as 132 nm (3.6 times that of Example 1), the surfactant had poor stability, was prone to agglomeration and floating, and uneven wetting of the pores led to local over-etching. In Comparative Example 12, cationic CTAB was used to replace nonionic APG. CTAB underwent Hofmann elimination degradation and deactivation in a strong alkali solution at 85°C; the positively charged head group reacted with SiO3² - Electrostatic binding with EDTMPS leads to competitive weakening of chelation and the formation of insoluble complex deposits. This comparative example, from the opposite perspective, verifies the rationality and appropriateness of the choice of nonionic wetting agents (alkyl glycosides and / or polyoxyethylene ethers) in this application—in the extreme chemical environment of high-temperature, strong-alkali etching systems, nonionic surfactants are the only suitable choice to achieve long-term stable wetting effects.
[0118] By comparing the system of Example 1 with Comparative Examples 1-12, it can be seen that the alkaline etching solution of this application is a ternary compound system with polyamino polyphosphonic acid chelating agents (containing at least two amino groups and at least two phosphonic acid groups) as the core, and alcohol amine agents (such as triethanolamine) and wetting agents (alkyl glycosides and / or polyoxyethylene ether nonionic surfactants) as auxiliary agents. Through the precise chemical matching and synergistic effect of each component, the etching solution achieves the etching of Ca²⁺ in the processing of soda-lime glass TGV under high temperature (70-110℃) and strong alkaline (KOH / NaOH) conditions. + / Mg² +Effective suppression of precipitation and high-quality forming of high aspect ratio vias. No core component in this ternary system can be easily replaced by other types of chemical substances—the phosphonic acid group of the chelating agent cannot be replaced by a carboxylic acid group (Comparative Examples 2, 6, 7), the polyaminopolyphosphonic acid structure cannot be replaced by a non-polyaminopolyphosphonic acid structure (Comparative Example 5), the single, highly efficient main chelating agent of polyaminopolyphosphonic acids cannot be replaced by a low-concentration multi-component mixture (Comparative Example 4), the hydroxyl auxiliary function of the alkanolamine agent cannot be replaced by pure amine (Comparative Example 8), and the nonionic structure of the wetting agent cannot be replaced by a cationic structure (Comparative Example 12). Furthermore, each component in this ternary system is indispensable—the absence of the chelating agent directly leads to precipitation blockage and process failure (Comparative Example 10), the absence of the alkanolamine agent leads to significant deterioration of wettability and etching uniformity (Comparative Example 9), and the absence of the wetting agent leads to severe deterioration of via consistency and roughness (Comparative Example 11).
[0119] Therefore, when using the alkaline etching solution of this application embodiment to etch the soda-lime glass substrate, the etching rate is significantly improved, the soda-lime glass substrate is stably straight through, without hole blockage or shrinkage, and the taper is excellent. The roughness of the inner wall of the through hole is low, meeting the requirements of high-end TGV metallization; the entire process is alkaline, avoiding the problems of fluoride precipitation, lateral corrosion, and taper loss of acid etching, and the etching process is stable and controllable.
[0120] The above description is merely a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A method for processing through holes in soda-lime glass, characterized in that, Includes the following steps: Laser modification is performed on the target area of the soda-lime glass to form a modified area that penetrates the soda-lime glass; The modified area is etched using an alkaline etching solution to form a through hole; The raw materials of the alkaline etching solution include an inorganic strong base, a chelating agent, a wetting agent, an alkanolamine agent, and water; the chelating agent includes polyamino polyphosphonic acid chelating agents and / or their salts containing at least two amino groups and at least two phosphonic acid groups.
2. The method for processing through holes in soda-lime glass according to claim 1, characterized in that, The raw materials of the alkaline etching solution, by mass fraction, include the following components: Inorganic strong base 10~40%; Chelating aid 1-3%; Wetting agent 0.1~2%; Alkyl amine auxiliaries: 0.1-1%; Water balance.
3. The method for processing through holes in soda-lime glass according to claim 1 or 2, characterized in that, The polyaminopolyphosphonic acid chelating adjuvants include one or more of ethylenediaminetetramethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, polyaminopolyethermethylenephosphonic acid, and hexamethylenediaminetetramethylenephosphonic acid; and / or, The wetting agent includes alkyl glycoside nonionic surfactants and / or polyoxyethylene ether nonionic surfactants; and / or, The alkanolamine adjuvants include one or more of monoethanolamine, diethanolamine, triethanolamine, methyldiethanolamine, and diisopropanolamine; and / or, The inorganic strong base includes sodium hydroxide and / or potassium hydroxide.
4. The method for processing through holes in soda-lime glass according to claim 3, characterized in that, The alkyl glycoside nonionic surfactants include C8-C14 alkyl glucosides and / or isomeric alcohol alkyl glycosides; and / or, The polyoxyethylene ether nonionic surfactants include one or more of AEO-7, AEO-9, and compound nonionic surfactants containing polyoxyethylene ethers.
5. The method for processing through holes in soda-lime glass according to claim 1 or 2, characterized in that, The wetting agent includes alkyl glycoside nonionic surfactants and polyoxyethylene ether nonionic surfactants, and the mass fraction of the wetting agent is 0.5~2%.
6. The method for processing through holes in soda-lime glass according to claim 1, characterized in that, The modified region is etched using an alkaline etching solution, which includes: immersing the laser-modified soda-lime glass in the alkaline etching solution, introducing air into the alkaline etching solution, controlling the temperature of the alkaline etching solution to 70~110℃, and etching the soda-lime glass under stirring conditions.
7. The method for processing through holes in soda-lime glass according to claim 6, characterized in that, The airflow rate is 0.3~1.0 L / min; and / or, The stirring speed is 400~1000 rpm / min.
8. The method for processing through holes in soda-lime glass according to claim 1 or 2, characterized in that, The lasers used for laser modification of target areas of soda-lime glass include picosecond lasers or femtosecond lasers.
9. The method for processing through holes in soda-lime glass according to claim 8, characterized in that, The pulse width of the laser is 800 fs to 5 ps; and / or, The energy of the laser is 50~150μJ; and / or, The frequency of the laser is 100~300kHz.
10. An alkaline etching solution for machining through-holes in soda-lime glass, characterized in that, The raw materials of the alkaline etching solution for processing through holes in soda-lime glass include an inorganic strong alkali, a chelating agent, a wetting agent, an alkanolamine chelating agent, and water. The chelating agent includes polyamino polyphosphonic acid chelating agents and / or their salts containing at least two amino groups and at least two phosphonic acid groups.
11. The alkaline etching solution for machining through-holes in soda-lime glass according to claim 10, characterized in that, The raw materials of the alkaline etching solution, by mass fraction, include the following components: Inorganic strong base 10~40%; Chelating aid 1-3%; Wetting agent 0.1~2%; Alkyl amine auxiliaries: 0.1-1%; Water balance.
12. The alkaline etching solution for machining through-holes in soda-lime glass according to claim 10 or 11, characterized in that, The polyaminopolyphosphonic acid chelating adjuvants include one or more of ethylenediaminetetramethylenephosphonic acid, diethylenetriaminepentamethylenephosphonic acid, polyaminopolyethermethylenephosphonic acid, and hexamethylenediaminetetramethylenephosphonic acid; and / or, The wetting agent includes alkyl glycoside nonionic surfactants and / or polyoxyethylene ether nonionic surfactants; and / or, The alkanolamine adjuvants include one or more of monoethanolamine, diethanolamine, triethanolamine, methyldiethanolamine, and diisopropanolamine; and / or, The inorganic strong base includes sodium hydroxide and / or potassium hydroxide.
13. The alkaline etching solution for machining through-holes in soda-lime glass according to claim 12, characterized in that, The alkyl glycoside nonionic surfactants include C8-C14 alkyl glucosides and / or isomeric alcohol alkyl glycosides; and / or, The polyoxyethylene ether nonionic surfactants include one or more of AEO-7, AEO-9, and compound nonionic surfactants containing polyoxyethylene ethers.
14. A soda-lime glass with through holes, characterized in that, The through hole is made using the soda-lime glass through hole processing method according to any one of claims 1 to 9.
15. The soda-lime glass with through holes according to claim 14, characterized in that, The depth-to-diameter ratio of the through hole is ≥80:1 and ≤150:1, and the roughness of the inner wall of the through hole is ≤50nm.